An Analysis of Fiscal Equity Provided by the JLARC System for Financing Public Schools: Commonwealth of Virginia 1987-88 to 1997-98 - Richard Salmon; Deborah Verstegen (Educational Considerations, 2001)
At the request of the Virginia Education Association (VEA), a 1990 study of the Virginia System of Public School Finance, Closing the Gap, contrasted the level of fiscal equity achieved by the Commonwealth for school year, 1988-89, with prior year, 1987-88.